2011
DOI: 10.1093/nar/gkr833
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the structural complexity in a single-stranded RNA tail: implications for efficient ligand binding in the prequeuosine riboswitch

Abstract: Single-stranded RNAs (ssRNAs) are ubiquitous RNA elements that serve diverse functional roles. Much of our understanding of ssRNA conformational behavior is limited to structures in which ssRNA directly engages in tertiary interactions or is recognized by proteins. Little is known about the structural and dynamic behavior of free ssRNAs at atomic resolution. Here, we report the collaborative application of nuclear magnetic resonance (NMR) and replica exchange molecular dynamics (REMD) simulations to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
92
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 78 publications
10
92
1
Order By: Relevance
“…We previously reported the dynamic properties of an isolated 12-nt ssRNA, hereafter referred to as SS, derived from a B. subtilis prequeuosine riboswitch (Eichhorn et al 2012a). We designed a ssRNA-helix junction construct variant containing the same 12-nt ssRNA connected to a GC-rich 22-bp hairpin capped with the thermodynamically stable cUUCGg tetraloop (E-SS) (Fig.…”
Section: Construct Design and Resonance Assignmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported the dynamic properties of an isolated 12-nt ssRNA, hereafter referred to as SS, derived from a B. subtilis prequeuosine riboswitch (Eichhorn et al 2012a). We designed a ssRNA-helix junction construct variant containing the same 12-nt ssRNA connected to a GC-rich 22-bp hairpin capped with the thermodynamically stable cUUCGg tetraloop (E-SS) (Fig.…”
Section: Construct Design and Resonance Assignmentsmentioning
confidence: 99%
“…Recently we showed using a combination of NMR spectroscopy and replica exchange molecular dynamics (REMD) simulations that the adenine-rich, 12-nucleotide (nt) ssRNA in the Bacillus subtilis prequeuosine riboswitch adopts, on average, an A-form-like conformation with an ordered 6-nt adenine core and gradually increasing flexibility toward the terminal ends (Eichhorn et al 2012a). Together with CD and UV/Vis melting experiments, these data indicated that the ssRNA is in equilibrium between an ordered A-form-like helical conformation and a highly disordered partially melted state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, MD has elucidated chemical features that stabilize ligand binding, the interactions that stabilize conformational endpoints, and features that facilitate conformational switching. Studies have been conducted on the SAM-I riboswitch (Huang et al 2009;Stoddard et al 2010;Doshi et al 2012;Hayes et al 2012;Huang et al 2013;Xue et al 2015), the SAM-II riboswitch (Kelley and Hamelberg 2010;Doshi et al 2012), the guanine riboswitch (Villa et al 2009;Sund et al 2014), the adenine riboswitch (Sharma et al 2009;Priyakumar and MacKerell 2010;Nozinovic et al 2014;Sund et al 2014), the GlmS riboswitch (Banáš et al 2010;Xin and Hamelberg 2010), and the preQ 1 -I and preQ 1 -III riboswitches (Petrone et al 2011;Banáš et al 2012;Eichhorn et al 2012;Gong et al 2014;Liberman et al 2015). Overall, these studies show the feasibility of using MD to understand riboswitch function and provide an opportunity to look for common themes in ligand binding and conformational dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the preQ 1 -II riboswitch represents a putative target for antibiotic intervention. Although preQ 1 class I (preQ 1 -I) riboswitches have been extensively investigated (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), preQ 1 class II (preQ 1 -II) riboswitches have been largely overlooked despite the fact that a different mode of ligand binding has been postulated (14).…”
mentioning
confidence: 99%